PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KOTA (Studi Pada Satuan Kerja Perangkat Daerah Kota Batu) - Susanti, Nonik Dwi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This research aims to examine the effect of accrual-based governmental accounting standards implementation and human resource competence on the quality of financial statements of Batu City. The objects of this study is 40 work units in Batu City. 130 data have been successfully collected distributing questionnaires to respondents, which are selected through purposive sampling technique. The data are analyzed using multiple linear regression method in SPSS20. The results show that the implementation of accrual-based governmental accounting standards and the competence of human resource have a positive effect on the quality of financial statements of the Local Government of Batu City.Keywords: Accrual-based governmenatal accounting standards, human resource competence, quality of financial statements of local government